The relationship between parenting patterns and the incidence of picky eating in preschool children at PAUD Islam Permatasari Tlogosari Semarang - Magdalena, Ainy; Astuti, Yuli; Aisyaroh, Noveri (Science Midwifery, 2024)
Preschool-age children are at risk of nutritional problems due to inappropriate eating habits, especially picky eating. Picky eating refers to a behavior in children where they have difficulty eating, causing anxiety for parents and caregivers. Factors that influence picky eating behavior include parenting styles. Inappropriate parenting styles, such as always spoon-feeding the child or not introducing vegetables early on, can worsen picky eating problems and affect the child's eating habits in the future. This study aims to identify parenting styles and the occurrence of picky eating in preschool children at PAUD Islam Permatasari Tlogosari Semarang, as well as to analyze the relationship between parenting styles and picky eating in children. The research method used in this study is quantitative analytical with a cross-sectional approach, using a questionnaire to identify maternal parenting styles and children's eating behavior. The research sample consisted of 92 parents of preschool children. The results of the study showed that in PAUD Islam Permatasari School in Tlogosari Semarang, the majority of maternal parenting styles towards preschool children tended to be authoritarian, reaching 31 (41.3%) out of the total sample. In addition, the majority of children did not experience picky eating, with a total of 43 (57.3%). Nevertheless, the results of the study revealed that there was not a significant relationship between the parenting styles of mothers (X) and the occurrence of picky eating behavior (Y) in preschool children at PAUD Islam Permatasari in Tlogosari Semarang. The p-value of 0.179 (>0.05) obtained further supports this conclusion.